Design of a Modern Luxury Connecting Bathroom for Children's Bedrooms in a Government Official Residence: An Internship Study at PT. KIND Indonesia - Nova Rosa Haryanto (Journal of Interdisciplinary Social Sciences and Humanities, 2026)
The independent internship program under MBKM (Merdeka Belajar Kampus Merdeka) serves as a strategic platform for students to enhance academic knowledge through direct practice in the design industry. This article reflects the author's experience during an internship at PT. KIND Indonesia, an interior and architectural design firm based in Jakarta. One of the projects handled by the author involved designing a modern luxury connecting bathroom that links two children's bedrooms in an official residence. The design process included analyzing user needs, developing visual concepts, selecting appropriate materials, and producing 3D visualizations. The use of marble-patterned granite and a neutral color palette created a clean and elegant atmosphere, tailored to the character of a government residence. This experience broadened the author's perspective on professional interior design practices and provided insight into how design solutions must be adapted to user requirements and project context. Technical challenges and ongoing revisions served as valuable learning opportunities in facing real-world industry dynamics.